Implementation of Electronic Records Management System (ERMS) at National Archive of Malaysia (ANM) / Ap Azli Bunawan, Raja Abdullah Yaacob and Nur Asyikeen Kamarudin - Bunawan, Ap Azli; Yaacob, Raja Abdullah; Kamarudin, Nur Asyikeen (Faculty of Information Management, 2014)
Electronic Records Management System (ERMS) is one of the most important aspects in managing electronic records. It was not only mend for digital forms of records but also be able to monitor both types either in physical or electronic forms. In this research, it was shown that the use of ERMS becomes a compulsory thing in managing the records in organizations. National Archive of Malaysia (ANM) was being chosen as an organization for a case study in this research. Then, the use of TRIM Context as a platform in managing the records at ANM becomes the strength of this research. While testing the software performance, ANM comes out with the standard and works in line with the ISO. Then, acceptance level of users towards the software was also being identified and discussed in the data analysis. Finally, this research has proven that an implementation of ERMS at ANM gives a positive impact to the organization, staff, and the software as well.